RNA Secondary Structure Representation Network for RNA-proteins Binding Prediction - Liu, Ziyi; Luo, Fulin; Du, Bo (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
RNA-binding proteins (RBPs) play a significant part in several biological processes in the living cell, such as gene regulation and mRNA localization. Several deep learning methods, especially the model based on convolutional neural network(CNN), have been used to predict the binding sites. However, previous methods fail to represent RNA secondary structure features. The traditional deep learning methods generally transform the RNA secondary structure to a regular matrix that cannot reveal the topological structure information of RNA. To effectively extract the structure features of RNA, we propose an RNA secondary structure representation network (RNASSR-Net) based on graph convolutional neural network (GCN) and convolution neural network (CNN) for RBP binding prediction. RNASSR-Net constructs the graph model derived from the RNA secondary structure to learn the topological properties of RNA. Then, it obtains the spatial importance of each base in RNA with CNN to guide the representation of the RNA secondary structure. Finally, RNASSR-Net combines the structure and sequence features to predict the binding sites. Experimental results demonstrate the proposed method outperforms a few state-of-the-art methods on the benchmark datasets and gets a higher improvement on the small-size data. Besides, the proposed RNASSR-Net is also used to detect the accurate motifs compared with the experimentally verified motifs, which reveals the binding region location and RNA structure interpretation for some biological guidance in the future.